Development of Green Oxidation Reactions Using Amine N-Oxide as Oxidizing Agents - Bannarak Khumraksa (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
Amine N-oxide is a reactive reagent commonly used as an oxidant and a co-oxidant in a variety of oxidation reactions. In recently years, the “Green Chemistry” concept has emerged as guidelines for the development of new synthetic methodologies and chemical processes which lead to reduction of environmental problem. Based on this criteria, this research aim to develop new greener methodologies for oxidation reactions using amine N-oxide as an oxidizing agent. The green synthesis strategies including microwave and ultrasound irradiation, ionic liquids, solvent-free reaction and the used of solid-supported reagent will be applied to improve the product yield and efficiency of the amine N-oxide oxidation. A various types of organic substances such as organic halides and alcohols will be used as the substrates. In the first study, N-methylmorpholine N-oxide (NMO) oxidation of organic halides was developed using ultrasonic and microwave as alternative energy source. The ultrasonic reaction was carried out in ultrasonic bath using 4.0 mole equivalent of NMO in dimethylsulfoxide (DMSO) solvent. A range of benzylic halides were smoothly converted to corresponding aldehydes within 10 min. However, the use of DMSO makes this condition less favorable from the green chemistry approach. Thus, another green procedure for organic halide oxidation was developed using ionic liquid as a solvent under microwave irradiation. A combination of microwave and ionic liquid provided rapid oxidation of benzylic halides to the corresponding aldehydes in good to excellent yields within a few minutes. The use of ionic liquid facilitates work-up procedure, while ionic liquid itself can be easily recovered and reused. Moreover, this new developed protocol was also efficiently applied with pyridine N-oxide (PyNO) in the same oxidation reaction, which resulted in good to excellent yield of aldehyde products. Since the use of solid supported reagents offers the ability to use excess quantities of reagents to drive reactions to completion and allows the ease of product isolation by simple filtration, new solid supported amine N-oxide were thus designed and synthesized for use as an oxidizing agent. Polymer ionic liquid supported methyl-piperazine N-oxide was prepared and coded as P4. These reagents were initially examined an oxidative efficiency in the oxidation of benzyl chloride. It was found that P4 can converted benzyl chloride into benzaldehyde in 41% under ultrasonic irradiation at room temperature for 1h. In the next study, an ultrasound technique was employed to develop a one-pot oxidation/reductive amination of benzyl halides under solvent-free condition. The method used 1.5 equiv. of NMO to convert organic halides to the corresponding carbonyl products before subsequent reductive amination in the presence of amines and NaBH4. Various benzylic halides together with a range of amines could be efficiently converted into the secondary and tertiary amine products in good to excellent yields without over alkylation or over oxidation. In attempts to convert alcohols to carbonyl compounds using NMO as an oxidant, both the Brønsted and Lewis acids were investigated as a catalyst in the microwave-assisted oxidation of alcohol in ionic liquid. Unfortunately, this attempt failed to give satisfied results by giving substantial amount of undesired toluene by-product. Thus, a new one-pot procedure for alcohol oxidation was developed utilizing iodination/oxidation sequence under ultrasonic irradiation. Through the reaction of alcohols with polymer supported PPh3 and I2, the iodo derivatives were generated which underwent oxidation with NMO to afford carbonyl compounds.